Taxonomic revision of the microleafhopper genus Naratettix Matsumura (Homoptera: Cicadellidae: Typhlocybinae) from Korea - Hossain, Md. Shamim; Kwon, Jin Hyung; Suh, Sang Jae; Kwon, Yong Jung (Zootaxa, 2019)
The genus Naratettix Matsumura, 1931 from Korea is revised. With the three previously recorded species, N. cheondungsanus sp. nov. is described as new to science, and N. ibukisanus Matsumura, 1931 is reported for the first time from Korea. Descriptions, illustrations and a key to the Korean Naratettix species are provided.